2010
DOI: 10.1063/1.3454244
|View full text |Cite
|
Sign up to set email alerts
|

TiO 2 nanotubes as a cold cathode for x-ray generation

Abstract: Here we report on an x-ray source based on titanium dioxide (TiO2) nanotubes grown by electrochemical oxidation. From the analysis of current-voltage characteristics of TiO2 electron emitter field emission nature of the current was confirmed. The threshold voltage and field enhancement factors were derived to be ∼1.8 V/μm and ∼8363, respectively. The current density was ∼4.0 mA/cm2 at ∼2.4 V/μm. The stability tests showed that the current stayed stable within 6% for more than 720 h. TiO2 nanotubes were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…The TNT can be used as a field emission electron source for generating X-ray radiation. It is not affected by exposure to O 2 and has a good electrical contact between TNT film and conductive Ti sheet [129].…”
Section: Doping Of Tnt With Other Elementsmentioning
confidence: 99%
“…The TNT can be used as a field emission electron source for generating X-ray radiation. It is not affected by exposure to O 2 and has a good electrical contact between TNT film and conductive Ti sheet [129].…”
Section: Doping Of Tnt With Other Elementsmentioning
confidence: 99%
“…One-dimensional (1D) metal oxide nanomaterials such as ZnO [1][2][3], SnO 2 [4,5], WO 3 [6], Fe 2 O 3 [7], and TiO 2 [8][9][10] have stimulated enormous attention for field emitters in the past decades due to their sharp tips, high aspect ratio, and superior antioxidation ability which can operate under unfavorable environment with relatively high oxygen partial pressure in their applications. Among various 1D metal oxide nanomaterials, TiO 2 nanotube arrays (TNAs) fabricated by anodization have attracted considerable attention for several reasons [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Here, CNTs doped with TiO 2 nanoparticles are used as electron emitters for improving FE uniformity, stability, and lifetime. TiO 2 is a wide bandgap (∼3.2 eV) semiconductor with outstanding mechanical, chemical and thermal stability, as well as a relatively low work function (3.9–4.5 eV) compared with CNTs (∼5 eV) 17. The FE properties of TiO 2 nanomaterails such as nanowires and nanotube arrays have been investigated 17–20, but many researches showed that the turn‐on field of TiO 2 nanomaterails are very high 19, 20.…”
Section: Introductionmentioning
confidence: 99%